CASSATION REVIEW OF THE REASONING OF THE JUDGMENT - Zamora Acevedo, Miguel (2023)
The investigation analyzes the problem related to the criminal challenge adopted in the admissibility phase of the criminal appeal, specifically on the non-observance or erroneous application of a legal, substantive or procedural precept. This, due to possible errors in the assessment of the evidence and determination of the factual premise. As a first problem, the dichotomy between the principle of immediacy and the need to review the ruling is addressed, pointing out the absence of contradiction in the analysis of evidentiary inferences in accordance with current procedural rules. Next, and as a second point, the relationship between the facts and the law is studied, pointing out the necessary link, which is affected by the design of the rules for admission of the appeal. From the above, making a reconstruction of the evidentiary reasoning used, it is shown that the review in cassation of issues related to the fact-law binomial is a requirement that arises from the need to review the ruling.